Hybrid external fixation with primary closure for a Gustilo-Anderson type III A proximal tibial fracture: a case report - Sulaiman, M.; Billah, S. M. Masum (International Journal of Research in Orthopaedics, 2026)
Open fractures of the proximal tibia are associated with a high risk of infection because of limited soft-tissue coverage and compromised vascularity. Although staged management with delayed internal fixation is commonly practiced, external fixation may serve as a definitive option in selected Gustilo-Anderson type IIIA injuries with adequate soft tissue condition. A 19-year-old male sustained a right proximal third open tibial fracture following a road traffic accident on 30 October 2023. Intravenous broad-spectrum antibiotics and tetanus prophylaxis were administered immediately upon admission. Surgical treatment was performed on 31 October 2023 using hybrid external fixation with primary wound closure. Early callus formation was noted at six weeks, and bridging callus across all cortices was confirmed at approximately eighteen weeks. The external fixator was removed on 05 March 2024 following confirmation of union, followed by short-term protective casting. Radiographs at twenty-three months demonstrated maintained alignment and complete cortical remodelling. Hybrid external fixation with primary wound closure may provide a reliable definitive treatment option for carefully selected Gustilo-Anderson type IIIA proximal tibial fractures when adequate debridement and stable fixation are achieved.